Benign Prostatic Hyperplasia and Clinical Prostate Cancer - Two New Components of the Metabolic Syndrome - Jan, Hammarsten (Current Hypertension Reviews, 2006)
The metabolic syndrome is a common generator of diseases in countries with western civilization lifestyles. Type 2 diabetes, atherosclerotic disease manifestations, hypertension, obesity, dyslipidaemia, hyperuricaemia, hyperinsulinaemia, dysfibrinolysis and microalbuminuria are considered to be established components of the metabolic syndrome. A clinical observation that obese and/or diabetic men appeared to have a greater prostate gland than men without these conditions generated a series of scientific investigations. An important finding was that benign prostatic hyperplasia (BPH), as measured by the total prostate gland volume or the annual BPH growth rate, was statistically associated with 17 out of 19 components of the metabolic syndrome. Another important finding was that clinical prostate cancer, as measured by stage, grade and PSA-value, was linked to seven of nine components of the metabolic syndrome. Furthermore, it was found that lethal clinical prostate cancer was associated with six (and two more with borderline statistical significance) of ten components of the metabolic syndrome. Still another important finding was that fasting plasma insulin was independently associated with both BPH and clinical prostate cancer. In conclusion, the results of these studies indicate that there is an association between the metabolic syndrome and two important urological tumors, namely BPH and clinical prostate cancer. The results also indicate that BPH and clinical prostate cancer may be regarded as two new components of the metabolic syndrome besides Type 2 diabetes, hypertension, atherosclerotic disease manifestations, obesity, dyslipidaemia and others. The studies also suggest that fasting plasma insulin is a promoter of both BPH and clinical prostate cancer. The results have generated the hypothesis that hyperinsulinaemia is a primary event in the development of both BPH and clinical prostate cancer. If the results can be confirmed in future studies, they would give rise to very significant practical implications in the medical care sector. This article is essentially a review of the findings of our research group over the last 15 years on the link between hyperinsulinaemia and related metabolic perturbations.
Keywords: Metabolic syndrome